Circulating endothelial cells are elevated in patients with type 1 diabetes mellitus - (:unkn) unknown (BIOSCIENTIFICA LTD, 2010)
Objective: Circulating endothelial cells (CECs) have emerged as vascular damage markers and are increased in type 2 diabetic patients. Since type 1 diabetes is associated with vascular damage, we hypothesized high CEC numbers in this patient population. Methods: Thirty-nine patients with type 1 diabetes and 39 controls were included. CECs were isolated using anti-CD146-coated Dynabeads, stained with Ulex lectin-1, and counted by fluorescence microscopy. Endothelial function was measured as flow-mediated dilation (FMD). Thiobarbituric acid reactive substances (TBARS), total glutathione levels (GSH), and paraoxonase (PON) activity levels were measured as oxidative stress markers. Results: Patients with type 1 diabetes mellitus had higher number of CECs (7.46 +/- 5.37 vs 2.13 +/- 1.13 cells/ml, P<0.001), lower FMD (7.87 +/- 2.19 vs 12.06 +/- 2.34%, P<0.001), higher TBARS (4.94 +/- 1.20 vs 3.07 +/- 0.75 nmol/MDA, P<0.001), lower GSH (206.12 +/- 98.06 vs 353.61 +/- 68.45 mM, P<0.001), and lower PON activity levels (89.10 +/- 17.82 vs 127.65 +/- 29.01U/l, P<0.001) as compared to controls. There was positive correlation between CEC numbers and HbAlc levels (r=0.49, P=0.002). CECs and fasting glucose levels were not correlated. There was no correlation between the number of CECs and FMD. Furthermore, there were no correlations between the number of CECs and TBARS, GSH and PON activity levels. Multiple regression analysis showed that HbAlc levels (r(2)=0.40, P<0.009) were associated with CEC numbers. Conclusion: CECs are elevated in patients with type 1 diabetes mellitus reflecting endothelial damage. This increase is dependent on long-term glucose control.
Keywords: SERUM PARAOXONASE ACTIVITY; HIGH-GLUCOSE; DEPENDENT VASODILATION; OXIDATIVE STRESS; PROGENITOR CELLS; GLYCEMIC CONTROL; DYSFUNCTION; APOPTOSIS; HYPERGLYCEMIA; GLUTATHIONE